2024
DOI: 10.1021/acsnano.3c11385
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Diffusion Kinetics to Reverse Propane/Propylene Adsorption in Zeolitic Imidazolate Framework-8

Linghe Yang,
Ying Liu,
Fang Zheng
et al.

Abstract: The separation challenge posed by propylene/ propane mixtures arises from their nearly identical molecular sizes and physicochemical properties. Metal−organic frameworks (MOFs) have demonstrated potential in addressing this challenge through the precision tailoring of pore sizes and surface chemistry. However, introducing modifications at the molecular level remains a considerable hurdle. This work presents an approach to reversibly tune the propylene/propane adsorption preference in zeolitic imidazolate frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the inflection point of pore opening moves from P / P 0 ∼ 0.60 (i.e., 7.76 kPa) at 293 K, to P / P 0 ∼ 0.40 (i.e., 6.74 kPa) at 298 K, and to P / P 0 ∼ 0.15 (i.e., 5.29 kPa) at 313 K (Figures a and S14). Compared with conventional examples that increasing temperature will delay the inflection point, , this opposite trend indicated that kinetic factors should play an important role in adsorption and structural transformation (possessing high energy barriers). , Obviously, there was large hysteresis in desorption isotherms (Figure S14), which should be attributed to strong guest–host interactions and framework flexibility . Moreover, even though MeOH molecules could coordinate onto the Ca sites in the structure, the measured adsorption enthalpy by differential scanning calorimetry (DSC) is −52.5 kJ·mol –1 (Figure S16), much higher (more positive) than that of the bond energy of Ca–O (−90 kJ·mol –1 ), which can be attributed to the energy compensation from framework flexibility. ,, …”
Section: Resultsmentioning
confidence: 91%
“…Interestingly, the inflection point of pore opening moves from P / P 0 ∼ 0.60 (i.e., 7.76 kPa) at 293 K, to P / P 0 ∼ 0.40 (i.e., 6.74 kPa) at 298 K, and to P / P 0 ∼ 0.15 (i.e., 5.29 kPa) at 313 K (Figures a and S14). Compared with conventional examples that increasing temperature will delay the inflection point, , this opposite trend indicated that kinetic factors should play an important role in adsorption and structural transformation (possessing high energy barriers). , Obviously, there was large hysteresis in desorption isotherms (Figure S14), which should be attributed to strong guest–host interactions and framework flexibility . Moreover, even though MeOH molecules could coordinate onto the Ca sites in the structure, the measured adsorption enthalpy by differential scanning calorimetry (DSC) is −52.5 kJ·mol –1 (Figure S16), much higher (more positive) than that of the bond energy of Ca–O (−90 kJ·mol –1 ), which can be attributed to the energy compensation from framework flexibility. ,, …”
Section: Resultsmentioning
confidence: 91%